Answer:
If b=-3 then the first expression is equal to 24 and the second expression is equal to -14.
If b=-2 then the first expression is equal to 8 and the second expression is equal to -36.
If b=10 then the first expression is equal to 440 and the second expression is equal to 324.
Yes, it is true.
Step-by-step explanation:
b=-3:
4b(b+1)=4(-3)(-3+1)=-12(-2)=24
(2b+7)(2b-8)=(2(-3)+7)(2(-3)-8)=(-6+7)(-6-8)=1(-14)=-14
b=-2:
4b(b+1)=4(-2)(-2+1)=-8(-1)=8
(2b+7)(2b-8)=(2(-2)+7)(2(-2)-8)=(-4+7)(-4-8)=3(-12)=-36
b=10:
4b(b+1)=4(10)(10+1)=40(11)=440
(2b+7)(2b-8)=(2(10)+7)(2(10)-8)=(20+7)(20-8)=27(12)=324
2 Colin is j = h with us like m with bisects gk is your answer
Answer:
-17x - 27
Step-by-step explanation:
Distributive property is the multiplication of the number outside the parenthesis and the ones inside.
-5(x + 4) + -3x + -9x + -7
-5x - 20 + -3x + -9x + -7
Combine like terms:
-5x - 20 + -3x + -9x + -7
-5x +-3x
-8x + -9x
-17x
-17x - 20 + -7
-20 + -7
-27
The answer is -17x - 27
Hope this helped.
Answer:
-27 = x
Step-by-step explanation:
4x+27=3x
Subtract 4x from each side
4x-4x+27=3x-4x
27 = -x
Multiply by -1
-27 = x
Let z = sin(x). This means z^2 = (sin(x))^2 = sin^2(x). This allows us to go from the equation you're given to this equation: 7z^2 - 14z + 2 = -5
That turns into 7z^2 - 14z + 7 = 0 after adding 5 to both sides. Use the quadratic formula to solve for z. The only solution is z = 1 (see attached image). Since we made z = sin(x), this means sin(x) = 1. All solutions to this equation will be in the form x = (pi/2) + 2pi*n, which is the radian form of the solution set. If you need the degree form, then it would be x = 90 + 360*n
The 2pi*n (or 360*n) part ensures we get every angle coterminal to pi/2 radians (90 degrees), which captures the entire solution set.
Note: The variable n can be any integer.